2005
DOI: 10.1111/j.1471-4159.2005.03088.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of oxidative stress in paraquat‐induced dopaminergic cell degeneration

Abstract: Systemic treatment of mice with the herbicide paraquat causes the selective loss of nigrostriatal dopaminergic neurons, reproducing the primary neurodegenerative feature of Parkinson's disease. To elucidate the role of oxidative damage in paraquat neurotoxicity, the time-course of neurodegeneration was correlated to changes in 4-hydroxy-2-nonenal (4-HNE), a lipid peroxidation marker. When mice were exposed to three weekly injections of paraquat, no nigral dopaminergic cell loss was observed after the first adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
156
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(178 citation statements)
references
References 31 publications
22
156
0
Order By: Relevance
“…Silver staining for neurodegeneration was not detected until 24 hours, peaked at 72 hours, and persisted through 120 hours. Similar results were seen from a time course study investigating oxidative stress and neurodegeneration using the paraquat model of PD (McCormack et al, 2005). These studies suggest that markers of oxidative stress are increased before neuronal degeneration is detected.…”
Section: Discussionsupporting
confidence: 74%
“…Silver staining for neurodegeneration was not detected until 24 hours, peaked at 72 hours, and persisted through 120 hours. Similar results were seen from a time course study investigating oxidative stress and neurodegeneration using the paraquat model of PD (McCormack et al, 2005). These studies suggest that markers of oxidative stress are increased before neuronal degeneration is detected.…”
Section: Discussionsupporting
confidence: 74%
“…Further evidence that oxidative stress is the predominant mechanism by which PQ causes toxicity is the generation of 4-hydroxynonenals in vivo. 27 It is possible to conclude from these studies that the mechanisms of toxicity of PQ in neuronal cultures, cell lines and non-neuronal cells (lung, kidney and hepatocytes) are similar. It is clear that a chemical that is capable of triggering redox cycling/oxidative stress will do it regardless of the cellular system in which it operates in the presence of an adequate electron donor.…”
Section: Pq Toxicity In Animal Models and The Underlying Mechanismsmentioning
confidence: 99%
“…PQ (1,1 0 -dimethyl 4,4 0 -bipyridinium in its reduced form) is a member of a chemical class known as bipyridyl derivatives, which includes diquat (1,1 0 -ethylene-2,2 0 -bipyridylium dibromide) and cyperquat that has the same structure as the MPTP metabolite MPP þ (see below). One-electron reduction of PQ [26][27][28][29] probably underlies its toxic effects in the lung after accidental ingestion. Reduced PQ is then rapidly reoxidized to its cation form by molecular oxygen with the formation of superoxide radicals in a classical redox-cycling reaction.…”
Section: Pq Toxicity In Animal Models and The Underlying Mechanismsmentioning
confidence: 99%
“…These findings are supported by numerous animal studies that have identified potential mechanistic links between pesticides and PD pathogenesis (Betarbet et al, 2000;Bloomquist et al, 2002;Caudle et al, 2005;Hatcher et al, 2007;Kitazawa et al, 2001Kitazawa et al, , 2003McCormack et al, 2005;Miller et al, 1999;Purkerson-Parker et al, 2001;Richardson et al, 2006;Thiruchelvam et al, 2003). Additionally, higher levels of pesticides have been identified in post-mortem PD brains versus age-matched controls (Corrigan et al, 1998(Corrigan et al, , 2000Fleming et al, 1994;Pennell et al, 2006).…”
Section: Introductionmentioning
confidence: 80%